The incidence, risk factors, and outcomes of symptomatic avascular necrosis of bone among Chinese pediatric patients with acute lymphoblastic leukemia - Calvin Pui Lun Hoo; Alex Wing Kwan Leung; Joyce Pui Kwan Chan; Yin Ting Cheung; Frankie Wai Tsoi Cheng; Terry Tin Wai Chow; Grace Kee See Lam; Sau Yin Ha; Alan Kwok Shing Chiang; Rever Chak Ho Li; Chi Kong Li (Cancer Medicine, 2023)
Abstract Background Avascular necrosis (AVN) of bone is a debilitating complication of pediatric patients with acute lymphoblastic leukemia (ALL). While it is extensively studied and reported in Western population, studies focused on Orientals are limited. This study aims to evaluate the incidence, risk factors, and clinical outcomes of AVN among Chinese children with ALL. Methods This study is a retrospective, territory‐wide population‐based cohort study of pediatric patients with ALL enrolled on one of the three consecutive ALL study protocols (ALL‐IC‐BFM 2002, CCLG‐ALL 2008, and CCCG‐ALL 2015). Results A total of 24 out of 533 pediatric subjects with ALL (4.5%) had symptomatic AVN. Age was the single most important risk factor associated with the development of AVN. Only three patients were below age of 10 at the time of diagnosis of ALL. The incidences of AVN in patients aged above and below 10 years were 18.2% ± 3.6% and 0.8% ± 0.5%, respectively, and were significantly different (p < 0.005). Treatment protocol, immunophenotype, and gender were not predictive of AVN. Among the 24 patients, five required orthopedic interventions in view of progressive and severe disease. For subjects with hip joints involvement, follow‐up assessments showed 12 of 22 hip joints had radiological progression over a median duration of 3.63 years. Seventeen of them did not have pain at the latest follow‐up and among patients with pain (n = 7), five did not experience any limitation on activities of daily living while two required use of walking aids or wheelchair. Conclusion The incidence of symptomatic AVN in Chinese ALL patients was comparable to other studies in Western population. Adolescent age more than 10 years old was recognized to be the most important factor for development of AVN. Significant proportion of patients had radiological progression over time with a small percentage of subjects had daily activities affected.